PENGARUH PENGGUNAAN ALAT PERAGA BATANG NAPIER TERHADAP PEMAHAMAN KONSEP PERKALIAN SISWA KELAS III SD NEGERI 21 PANYULA - Sudarto, Sudarto; Muhammad Idris Jafar; Nurul Mutmainal Khaeraat (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2024)
This research is a pre-experimental research which aims to determine whether there is or not the use of napier rods has a significant effect o the students' ability in understanding the multiplication concept. The research design used was one group pretest-posttest design. The population in this study were all of the 3th Grade Studentat SD Negeri 21 Panyula with the sample of 29 students selected using a saturated sampling technique. The data collection technique used was a test to determine the ability of understanding in the multiplication concept before and after using the napier rod prop. The data analysis techniques used were a descriptive and inferential statistical analysis techniques. Based on the results of descriptive statistical analysis, the average students' ability in understanding the multiplication concept before and after using Napier rod props was of 57.14 and 83.34, respectively. Based on the results of inferential statistical analysis using the paired samples t test, tcount = 13.701 and ttable = 1.701. Because tcount > ttable, so there was a significant difference in students' understanding of the multiplication concept before and after using Napier rod props in the 3th Grade at SD Negeri 21 Panyula. Conclusion: the use of napier rod props had a significant effect on the ability in understanding the multiplication concept of the 3th Grade at SD Negeri 21 Panyula, Tanete Riattang District, Bone Regency